A Study on HR Challenges Facing by BFSI Sector - Kaur, Rajwinder (Gyan Management Journal, 2021)
BFSI sector is important sector of India economy. BFSI stands for banking, financial services and insurance. This sector helps to provide wide range of financial services and products to customers.Without this sector’s effective performance, no other sector in the economy perform effectively. BFSI sector represent the major portion of the India economy. For the smooth running of this sector, there are many departments which work for improving the efficiency of this sector. HR is one of important segment in BFSI sector. Without the effective performance and activities of HR, the sector can’t work effectively and satisfy customers. But HR also faces challenges in BFSI sector. The paper is an attempt to HR challenges in BFSI sector. Many challenges are identified through the study and examination of previous studies. Paper will also put light on various suggestions and strategies to dilute these HR challenges in BFSI sector.